2019
DOI: 10.1016/s0140-6736(18)32989-1
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, hyaluronan-selected intracytoplasmic sperm injection for infertility treatment (HABSelect): a parallel, two-group, randomised trial

Abstract: Summary Background Sperm selection strategies aimed at improving success rates of intracytoplasmic sperm injection (ICSI) include binding to hyaluronic acid (herein termed hyaluronan). Hyaluronan-selected sperm have reduced levels of DNA damage and aneuploidy. Use of hyaluronan-based sperm selection for ICSI (so-called physiological ICSI [PICSI]) is reported to reduce the proportion of pregnancies that end in miscarriage. However, the effect of PICSI on livebirth rates is uncertain. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 18 publications
0
65
2
Order By: Relevance
“…Overcoming this challenge is fundamental in guiding the development of assisted reproduction, and much has already been done. Over the last few years, there have been growing outstanding contributions in the high-quality scientific literature aimed at disentangling the effective from the non-effective interventions that have entered into clinical practice ( Chen et al , 2016 ; El-Toukhy et al , 2016 ; Smit et al , 2016 ; Wang et al , 2017 ; Farquhar et al , 2018 ; Shi et al , 2018 ; Smith et al , 2018 ; Vuong et al , 2018 ; Lensen et al , 2019 ; Miller et al , 2019 ; Wei et al , 2019 ).…”
Section: The Still Wobbly Evidence Base Of Ivfmentioning
confidence: 99%
“…Overcoming this challenge is fundamental in guiding the development of assisted reproduction, and much has already been done. Over the last few years, there have been growing outstanding contributions in the high-quality scientific literature aimed at disentangling the effective from the non-effective interventions that have entered into clinical practice ( Chen et al , 2016 ; El-Toukhy et al , 2016 ; Smit et al , 2016 ; Wang et al , 2017 ; Farquhar et al , 2018 ; Shi et al , 2018 ; Smith et al , 2018 ; Vuong et al , 2018 ; Lensen et al , 2019 ; Miller et al , 2019 ; Wei et al , 2019 ).…”
Section: The Still Wobbly Evidence Base Of Ivfmentioning
confidence: 99%
“…A number of studies have observed that the use of ICSI mitigated the effect of increased sperm DNA fragmentation (51, 52). The recent large hyaluronan-selected intracytoplasmic sperm injection for infertility treatment randomized controlled trial found no improvement in live birth but noted a significant reduction in miscarriage when using physiological ICSI rather than conventional ICSI (57).…”
Section: Figure 11mentioning
confidence: 99%
“…PICSI is therefore not recommended for routine clinical care. 78 The hypo-osmotic swelling (HOS) test evaluates the functional integrity of the sperm plasma membrane and can be useful to assess sperm viability if motility is very poor. Live spermatozoa placed in hypo-osmotic media swell, particularly the tail, because water and small compounds influx into the cytoplasm.…”
Section: New Developments In Sperm Selection In Artmentioning
confidence: 99%